Estudo do efeito da dopagem da alumina com Cério em catalisadores Pt/CeZrO2/Al2O3 na reação de oxidação parcial do Metano - Silva, Fabiano de Almeida (2007)
The transformation of methane into liquid fuels has drawn a lot of attention in the last years due to both economical and environmental concerns. Currently, the main route to obtain synthesis gas from methane is the steam reforming. The major problems associated with this route are the high temperatures and pressures required. Nowadays, the partial oxidation of methane has been considered as a potential process to generate synthesis gas, because it is slightly exothermic and it can give reasonable conversions at atmospheric pressure. However, it is crucial to have catalysts with high activity, selectivity and above all, stability even when submitted to the high reaction temperatures and space velocities. These characteristics can be obtained with a high metallic dispersion, a continuous regeneration of the catalytic surface and a stable support. Therefore, this work has as objectives to study the effect of cerium addition as a doping element for the alumina, with the purpose of increasing the thermal and mechanical stability of this support, and to study the effects of different noble metal loadings on Pt/CeO2/Al2O3 and Pt/CeZrO2/Al2O3 catalysts. The influence of different space velocities on the catalytic performance was also evaluated. The aluminas were obtained by the calcination of aluminum hydroxide (bohemite) at 873 and 1173 K. After this, the sample calcined at 873 K was doped with 1 wt% of cerium and calcined at 1173 K. The cerium and cerium-zirconium oxides, with 19 wt % of CeO2 or CeZrO2 and Ce/Zr =1, were added to the alumina through wet impregnation in a rotavapor. The platinum loadings added were 1.5, 1.0 and 0.5 wt% by incipient wetness impregnation. The samples supported on the doped alumina presented larger values of BET surface area, with the CeZrO2 based catalyst presenting the largest value. Even with different BET surface areas, the metallic dispersions, measured by the dehydrogenation of cyclohexane reaction, were similar for all catalysts containing 1.5 wt% of platinum. For the samples with smaller Pt content the metallic dispersions were higher, as expected. The X-ray diffraction analysis showed a smaller average particle size of cerium oxide for the samples containing zirconium. This technique also showed the formation of a homogeneous solid solution for the catalysts based on ceria-zirconia supported on the doped alumina. The H2 and O2 consumptions were determined by temperature programmed reduction and by oxygen storage capacity respectively. The results showed that the 0.5%Pt/CeZrO2/Al2O3-doped, 1.0%Pt/CeZrO2/Al2O3-doped and 1.5%Pt/CeZrO2/Al2O3-doped catalysts presented superior redox capacities when compared to the other samples. The catalytic tests showed that the ideal space velocity for the catalysts was 522 h-1. The use of smaller Pt contents lead to deactivation. Therefore, the best performance was obtained for the 1.5%Pt/CeZrO2/Al2O3-doped catalyst that has the largest platinum content, the presence of a homogeneous solid solution, good metal dispersion and a high BET surface area.